2023
DOI: 10.1021/jacs.3c05234
|View full text |Cite
|
Sign up to set email alerts
|

Shear Stress Triggers Ultrathin-Nanosheet Carbon Nitride Assembly for Photocatalytic H2O2 Production Coupled with Selective Alcohol Oxidation

Qi Li,
Yanqing Jiao,
Yunqi Tang
et al.

Abstract: Coupled photocatalysis without cocatalysts can maximize the utilization of photons and atoms, which puts forward higher demands on photocatalysts. Polymeric carbon nitride (CN) has become the most promising photocatalyst, but still suffers from major drawbacks of insufficient catalytic sites and low quantum efficiency. Herein, we report a fluid shear stress-assisted molecular assembly to prepare ultrathin-nanosheet-assembled acanthospherelike CN (ASCN) with nitrogen vacancy (Nv) and carbonyl modification. Shea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(38 citation statements)
references
References 62 publications
0
38
0
Order By: Relevance
“…The active species capture experiments investigated the active substances that play a major role in the photocatalytic system of 2% α-Fe 2 O 3 /TDCN. The different ROS generated in the reaction system can be characterized using a capture agent in principle . 10 mM of methanol (MeOH) and tert -butanol (TBA), 10 mM of furfuryl alcohol (FFA), 10 mM of l -ascorbic acid ( l -AA), and 10 mM of ethylenediaminetetraacetic acid disodium salt (EDTA·2Na) were used for capturing • OH, 1 O 2 , • O 2 – , and h + , respectively (Figure a). , It can be observed that the effects of adding two different • OH trapping agents (MeOH, TBA) on the reaction system were fragile, which represents a small role in removing • OH from the system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The active species capture experiments investigated the active substances that play a major role in the photocatalytic system of 2% α-Fe 2 O 3 /TDCN. The different ROS generated in the reaction system can be characterized using a capture agent in principle . 10 mM of methanol (MeOH) and tert -butanol (TBA), 10 mM of furfuryl alcohol (FFA), 10 mM of l -ascorbic acid ( l -AA), and 10 mM of ethylenediaminetetraacetic acid disodium salt (EDTA·2Na) were used for capturing • OH, 1 O 2 , • O 2 – , and h + , respectively (Figure a). , It can be observed that the effects of adding two different • OH trapping agents (MeOH, TBA) on the reaction system were fragile, which represents a small role in removing • OH from the system.…”
Section: Resultsmentioning
confidence: 99%
“…The different ROS generated in the reaction system can be characterized using a capture agent in principle. 63 10 mM of methanol (MeOH) and tert-butanol (TBA), 10 mM of furfuryl alcohol (FFA), 10 mM of L-ascorbic acid (L-AA), and 10 mM of ethylenediaminetetraacetic acid disodium salt (EDTA•2Na) were used for capturing…”
Section: Optical and Electrochemicalmentioning
confidence: 99%
“…[ 33,34 ] Figure S1h (Supporting Information) demonstrates the deconvoluted peaks of N 1s spectra, containing ‐C = N‐C, N─C 3 , C─N─H, and π‐ ‐ π * in the systems. [ 35,36 ] The peak from N 1s spectra without deconvolutions of FCN, CCN, and BCN exhibit the right shift to a lower binding energy region, proving the modified systems gain more free electrons than the pristine CN, improving catalytic outcomes. Besides, the calculated ratio of N‐C 3 and C‐N‐H area of modified samples from XPS in Figure S1i (Supporting Information) witness a decrease, recommending the large concentration of primary amine moieties anchored on g‐C 3 N 4 surfaces of the modified samples in contrast with the pristine CN.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, polymer carbon nitride (g-C 3 N 4 ) has the advantages of nontoxicity, no secondary pollution, visible light response, stability, and low cost; moreover it has been widely used in the photocatalytic conversion of solar energy, such as hydrogen and oxygen production from photocatalytic water-splitting, selective organic photosynthesis, and degradation of organic pollutants, thus attracting people's attention. 10–13 However, bulk g-C 3 N 4 suffers from poor charge separation, insufficient visible light absorption, and few catalytic sites, which significantly reduces the photocatalytic efficiency. 14–16 One of the prevailing approaches in photocatalytic studies involves the integration of g-C 3 N 4 nanosheets with other semiconductors to fabricate heterojunctions.…”
Section: Introductionmentioning
confidence: 99%